ISLAMIC CHARACTER EDUCATION IN THE DIGITAL AGE: A STUDY OF INDONESIAN STATE ISLAMIC UNIVERSITIES - Mohammad Syairozi Dimyathi; Fatihunnada Fatihunnada; Bambang Ruswandi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the structure and level of Islamic character education among students of State Islamic Higher Education Institutions in Indonesia. Islamic character education plays an important role in shaping students’ religious identity and ethical behavior in Islamic higher education. However, empirical studies examining its multidimensional structure and the contribution of each dimension remain limited. This research used a quantitative survey approach involving PTKIN students from Jakarta, West Java, and Banten. Data were analyzed using Second-Order Confirmatory Factor Analysis (CFA) within the Partial Least Squares–Structural Equation Modeling (PLS-SEM) framework. The findings show that the overall level of Islamic character education among students is moderate to high, indicating that Islamic values have been reasonably internalized in students’ academic and social lives. All five dimensions significantly contribute to the construct, with love of knowledge emerging as the most dominant factor, followed by obedience and compliance, spirituality, moral and ethical values, and social responsibility. These findings highlight the importance of intellectual orientation and academic culture alongside religious practices and moral values. This study contributes to the conceptual understanding of Islamic character education and recommends strengthening integrative character education through academic culture, religious activities, and student social engagement in institutions.